Immunoconglutinin and Complement Studies in Congenital Nephrotic Syndrome and Nephritis of Henoch-Schönlein Purpura in Children. Issue 250 (December 1971) - Shulman, S. T.; Barratt, T. M.; Soothill, J. F.
Abstract : Evidence of complement activation in 6 children with congenital nephrotic syndrome and 9 children with nephritis associated with Henoch-Schönlein purpura was sought by estimating the concentration and by immunoelectrophoretic analysis of the complement component C3, and by immunoconglutinin titration (IK: an autoantibody to reacted complement components). IK and quantitative C3 levels did not differ significantly from control values in either disease; in vivo C3 conversion was not detected in plasma from congenital nephrotic patients, but was present in 2 of 9 patients with Henoch-Schönlein nephritis. The data do not provide consistent evidence of complement involvement in either disease.